Analisis Pembelajaran Menyenangkan di Kelas 1 SDN Karangrejo 02 Semarang melaui Kurikulum Merdeka - Asih, Nur Amalia Septi; Fajriyah, Khusnul; Saputra, Henry Januar (TSAQOFAH, 2023)
Learning in the independent curriculum is designed to suit the needs and environmental conditions, and is relevant to the current developments. Thus, it is important for us to find learning methods that can create a fun and interesting atmosphere for students in participating in the learning process. This research was conducted with the aim of seeing how far the transformation of fun learning can be carried out through the implementation of the Independent Curriculum in class 1 at SDN Karangrejo 02 Semarang. This study used a qualitative approach with a descriptive research type. Data collection was carried out through interviews, observation, and data collection from documents related to the implementation of learning with the Independent Curriculum. The collected data was analyzed through four stages, namely data collection, data condensation, data presentation, and drawing conclusions. Based on the results of the study, there were significant changes in learning practices after the implementation of the Independent Curriculum. The Merdeka curriculum enables students to learn through an active, creative and experience-based approach. The teacher encourages students to learn through exploration, experimentation, and discussion, so that students feel free to explore knowledge. Educational game integration is also carried out in learning to make it more fun and interesting. Although the implementation of the Merdeka Curriculum faces challenges, such as preparing and developing materials suitable for this innovative learning approach, training and mentoring for teachers is considered important to help them implement this curriculum effectively. The hope is that the Merdeka Curriculum can form a generation that has a high interest in learning, developing creativity, and strong independence. With fun and student-centered learning, it is hoped that student achievement can increase.